Anti-Ro/SSA Antibodies and the Autoimmune Long-QT Syndrome - Lazzerini, Pietro Enea; Laghi-Pasini, Franco; Boutjdir, Mohamed; Capecchi, Pier Leopoldo (Frontiers in Medicine, 2021)
Autoimmunity is increasingly recognized as a novel pathogenic mechanism for cardiac arrhythmias. Several arrhythmogenic autoantibodies have been identified, cross-reacting with different types of surface proteins critically involved in the cardiomyocyte electrophysiology, primarily ion channels (autoimmune cardiac channelopathies). Specifically, some of these autoantibodies can prolong the action potential duration leading to acquired long-QT syndrome (LQTS), a condition known to increase the risk of life-threatening ventricular arrhythmias, particularly Torsades de Pointes (TdP). The most investigated form of autoimmune LQTS is associated with the presence of circulating anti-Ro/SSA-antibodies, frequently found in patients with autoimmune diseases (AD), but also in a significant proportion of apparently healthy subjects of the general population. Accumulating evidence indicates that anti-Ro/SSA-antibodies can markedly delay the ventricular repolarization via a direct inhibitory cross-reaction with the extracellular pore region of the human-ether-a-go-go-related (hERG) potassium channel, resulting in a higher propensity for anti-Ro/SSA-positive subjects to develop LQTS and ventricular arrhythmias/TdP. Recent population data demonstrate that the risk of LQTS in subjects with circulating anti-Ro/SSA antibodies is significantly increased independent of a history of overt AD, intriguingly suggesting that these autoantibodies may silently contribute to a number of cases of ventricular arrhythmias and cardiac arrest in the general population. In this review, we highlight the current knowledge in this topic providing complementary basic, clinical and population health perspectives.